2020
DOI: 10.1038/s41467-020-15895-5
|View full text |Cite
|
Sign up to set email alerts
|

SYNERGISTIC ON AUXIN AND CYTOKININ 1 positively regulates growth and attenuates soil pathogen resistance

Abstract: Plants as non-mobile organisms constantly integrate varying environmental signals to flexibly adapt their growth and development. Local fluctuations in water and nutrient availability, sudden changes in temperature or other abiotic and biotic stresses can trigger changes in the growth of plant organs. Multiple mutually interconnected hormonal signaling cascades act as essential endogenous translators of these exogenous signals in the adaptive responses of plants. Although the molecular backbones of hormone tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 104 publications
1
21
0
Order By: Relevance
“…Auxin and cytokinin action are closely interwoven and each of the two hormone influences the status of the other at multiple layers and through multiple signaling pathways, mostly in an antagonistic fashion ( Dello Ioio et al, 2008 ; Müller and Sheen, 2008 ). Components of that largely unknown network continue to be discovered, such as SYAC1 very recently ( Hurný et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Auxin and cytokinin action are closely interwoven and each of the two hormone influences the status of the other at multiple layers and through multiple signaling pathways, mostly in an antagonistic fashion ( Dello Ioio et al, 2008 ; Müller and Sheen, 2008 ). Components of that largely unknown network continue to be discovered, such as SYAC1 very recently ( Hurný et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this way, these two hormones determine, to a large extent, the overall plant phenotype. Other important plant traits including organogenesis and resistance to biotic and abiotic stresses are also auxin-/CK-dependent [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. In the 21st century, great progress has been achieved in dissecting the molecular mechanisms of auxin and CK perception and signal transduction [ 2 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the in-depth analysis of auxins and CKs pathways has revealed that multiple players are involved in the crosstalk of these two hormones, fine-tuning their levels of auxins and cytokinins in plants [ 6 ]. The cytokinins biosynthesis is positively modulated by auxins via direct control of the ISOPENTENYL TRANSFERASE (IPT) genes transcript accumulations, which is mediated by the AUXIN RESPONSE FACTOR 19 (ARF19) transcription factor [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the available literature with the recent findings sheds light on the involvement of both auxin and cytokinin pathway genes in leaf development in plants. However, the available literature is not sufficient for understanding the underlying molecular mechanisms [ 6 , 10 ].…”
Section: Introductionmentioning
confidence: 99%